Aplikasi Filantropi Dalam Ekonomi Islam - Herlina, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Philanthropy is a concept that has been contained in Islam, which aims for good (al-birr), seeing the different social and economic levels of society, ideas or concepts of philanthropy among people. The effectiveness of philanthropy in reducing social inequality cannot be separated from the role of philanthropic institutions that manage these activities. The potential sourced is one of the alternatives for a community group to reduce the social gap from philanthropy by implementing the distribution of capital to those who cannot afford it, so that it can play a role in economic activity, as a producer in increasing income. Poverty is an interesting theme to discuss, especially among social scientists. Many studies offer solutions to alleviate poverty, but the face of poverty still exists amid the dynamics of changing times. The efforts to tackle the problem of poverty have been continuously carried out by experts throughout the ages in an effort to find the ideal form of poverty alleviation. The theme of poverty is studied not only by developing countries but also developed countries. Before getting to know scientific studies on the problem of poverty, people had carried out a tradition that responded to the problem of poverty in the form of gifts. The activity of